Systematic study on reinforced concrete structures under progressive collapse - Lim, Namyo Salim (2017)
Due to the rapid increase of terrorist threats, the ability of a building to mitigate progressive collapse is of key interest to government agencies. Alternate Load Path approach is one of the direct methods to assess and quantify the resistance of building against collapse by evaluating the bridging resistance of the structure under notional removal of major load-bearing elements. This research conducted a systematic study on the structural behaviour and the development of secondary load-carrying mechanism in reinforced concrete (RC) structures starting from simple 2-D RC frames to more complete 3-D frame-slabs. Three series of experimental tests, i.e. 2-D RC frame tests, 3-D RC frame tests, and 3-D RC frame-slab tests under single column removal scenario were conducted to investigate structural behaviour and development of load-resisting mechanisms in each configuration. The specimens were loaded on a single point above the removed column until distinct failure was observed. In 2-D RC frame tests, the effects of horizontal restraint and reinforcement detailing on the behaviour and load-carrying capacity of the double-spanning beam were investigated. In 3-D RC frame tests, the presence of direct and compatibility torsions, as well as the interactions among the 3-D connected beams were studied. Lastly, the contributions of slabs to the 3-D frame substructures were identified in 3-D RC frame-slab tests. From the tests, inadequate restraint (penultimate column removal scenario) and the presence of torsion hindered capacities of beams, especially catenary action. In frame and frame-slabs specimen with adequate restraint and negligible torsion, the significances on the development of catenary action in beams and tensile membrane action in slabs in increasing the progressive collapse resistance of RC structures were identified. Numerical studies by employing fibre and plate elements in the modelling of beams and slabs, respectively, demonstrate the efficiency and reliability of this approach in simulating behaviour and resistance of RC substructures under progressive collapse (involving material and geometric non-linearity). The validated numerical models are employed to carry out further analyses such as multi-storey 2-D RC frames to identify the participation and interaction among each storeys and unequal beams in 3-D RC frames (common in building) to identify the effect of span and reinforcement ratio. Finally, a simplified analytical model is developed to predict the overall load capacity (response) of individual frames and slabs, as well as their combined capacities in frame-slab systems. This systematic study consisting of experimental, numerical, and analytical works of 2-D frames to 3-D frame-slabs is essential in supporting and improving the design approaches in current progressive collapse guidelines.